2022
DOI: 10.35799/jbl.v12i1.36437
|View full text |Cite
|
Sign up to set email alerts
|

Penanda DNA: Uji Halal pada Makanan Olahan Daging Menggunakan Primer Multiplex PCR (Polymerase Chain Reaction)

Abstract: Multiplex-PCR (mPCR) is a technique that is gaining popularity due to its ability to detect multiple species in a single tube, resulting in faster results with more efficient and cost-effective resources than the conventional PCR method. This study aimed to design mPCR genetic markers for the detection of bovine/rat/chicken/pork organisms in processed foods. The procedure was divided into two stages: in silico and in vitro. The primers were designed based on mitochondrial cytochrome genes obtained from the NCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…DNA bands that are formed in the mix 1 and mix 2 columns have different product sizes according to their respective target lengths. After the visualization process using the electrophoresis method, the target DNA bands will separate specifically which can be seen based on the thickness of the target DNA, and the thickness of the target DNA formed is based on the weight and amount of the targeted DNA [22].…”
Section: Primer Specificity Test For Multiplex Pcr Methodsmentioning
confidence: 99%
“…DNA bands that are formed in the mix 1 and mix 2 columns have different product sizes according to their respective target lengths. After the visualization process using the electrophoresis method, the target DNA bands will separate specifically which can be seen based on the thickness of the target DNA, and the thickness of the target DNA formed is based on the weight and amount of the targeted DNA [22].…”
Section: Primer Specificity Test For Multiplex Pcr Methodsmentioning
confidence: 99%
“…The results of research by Dzikrina et al (2022) have successfully used m-PCR and multiplex primers that produce amplicons with the size of chicken primer 272 bp, beef primer 522 bp, rat primer 622 bp, and pork primer 588 bp. However, the visualization of m-PCR products by electrophoresis on a 1.5-2.0% agarose gel showed that the amplicon from the pig, Beef, and rat primers could not be clearly distinguished.…”
Section: H a Y At I H A Y At Imentioning
confidence: 99%
“…Beef and pork primers were designed using the mitochondrial genome sequences of cattle (Bos taurus) and pigs (Sus scrofa) from the NCBI Genebank site (https://www.ncbi.nlm.nih.gov/) with the "complete genome" category. In contrast, rat and chicken primers used the sequences from Dzikrina et al 2022. After the Beef and pork primers were successfully redesigned, the sequence homology test was carried out with BLAST on the database contained on the NCBI website.…”
Section: Primary Designmentioning
confidence: 99%